Teaching across borders: A collaborative inter-racial "border" pedagogy in adult multicultural education classes. - Elizabeth J. Tisdell; Clarice Perry (Adult Education Research Conference, 1997)
This qualitative action research study examined how power dynamics were manifested between and among instructors and students in two graduate level classes team-taught by a black and a white female co-instructors where diversity and equity issues in education was the primary course content. The study also attempts to identify adult education practices that lead to growth and social change among participants in such classes that are at times both uncomfortable and controversial.